Study and design an electoral system based on blockchain technology - MEKKI, Ala eddine; Supervisor: Moussaoui, Adel (University of M'sila, 2023)
This thesis studies and explores how blockchain can be used to help make the electoral process run more transparently, more secure, and more efficiently. By addressing the known limitations of conventional voting methods, the thesis suggests a promising new blockchain-based voting system. Using Ethereum’s ERC20 token standard, providing secure and transparent elections. According to the research results, the implementation of a blockchain-based electoral system can make a big contribution to better voting procedures, reducing the risk of fraud and manipulation. The decentralized aspect of blockchain helps to make the voting process more democratic. Overall, this research serves to inform this in election by pointing to the power of blockchain technology to help build a voting process that is at once more efficient, more secure, and more transparent.